Brain changes after learning to read and play music - Stewart, Lauren; Henson, Rik; Kampe, Knut; Walsh, Vincent; Turner, Robert; Frith, Uta (NeuroImage, 2003)
Musically naive participants were scanned before and after a period of 15 weeks during which they were taught to read music and play the keyboard. When participants played melodies from musical notation after training, activation was seen in a cluster of voxels within the bilateral superior parietal cortex. A subset of these voxels were activated in a second experiment in which musical notation was present, but irrelevant for task performance. These activations suggest that music reading involves the automatic sensorimotor translation of a spatial code (written music) into a series of motor responses (keypresses).
Keywords: Adult; Brain; Female; Humans; Image Processing, Computer-Assisted; Learning; Magnetic Resonance Imaging; Male; Motor Skills; Music; Parietal Lobe; Reaction Time; Reading